Cropping systems in the subhumid zone of Nigeria - Powell, J.M. (International Livestock Centre for Africa, 1986)
Reports findings of baseline studies as size of cultivated area, cropping patterns, management in relation to fallowing and labour & other inputs, yields and constraints to increasing grain & forage production among traditional crop farmers and Fulani agropastoralists at Abet & Kurmin Biri, both in subhumid Nigeria.